2020
DOI: 10.22271/chemi.2020.v8.i5y.10565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone and sulphur dioxide as postharvest treatment to control Rhizopus rot and quality maintenance of table grape (Vitis vinifera L.)

Abstract: Table grape is one of the most important fruits which is subjected to fungal decay during post-harvest handling, transit and storage. An investigation was made to evaluate ozone (O3) fumigation at the concentration of 7274.4µL L -1 , 5455.8µL L -1 and 3637.2µL L -1 and sodium metabisulfite (SMB) as Indian grape guard, African grape guard and SMB powder pouches (0.5g/500g fruit) against Rhizopus rot and their effect on quality of table grapes under ambient storage (33±2°C, RH-37±5%, 12 d). The results revealed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Relevant research has suggested that 1-MCP treatment is capable of effectively inhibiting the increase of firmness and lignin during fruit and vegetable storage, which is achieved by inhibiting lignin biosynthesis and its enzyme activity [75]. Research has shown that SO 2 delays the postharvest senescence of fruits and vegetables [76]. At the later stage of storage, 1-MCP treatment and SO 2 treatment significantly inhibited POD and PAL activities (Figure 7A,B), and the relative gene expression changes further verified the above result (Figure 8D,E).…”
Section: Lignificationmentioning
confidence: 99%
“…Relevant research has suggested that 1-MCP treatment is capable of effectively inhibiting the increase of firmness and lignin during fruit and vegetable storage, which is achieved by inhibiting lignin biosynthesis and its enzyme activity [75]. Research has shown that SO 2 delays the postharvest senescence of fruits and vegetables [76]. At the later stage of storage, 1-MCP treatment and SO 2 treatment significantly inhibited POD and PAL activities (Figure 7A,B), and the relative gene expression changes further verified the above result (Figure 8D,E).…”
Section: Lignificationmentioning
confidence: 99%